Activated Protein C Drives the Hyperfibrinolysis of Acute Traumatic Coagulopathy. (January 2017) - Davenport, Ross A.; Guerreiro, Maria; Frith, Daniel; Rourke, Claire; Platton, Sean; Cohen, Mitchell; Pearse, Rupert; Thiemermann, Chris; Brohi, Karim
Abstract : Background: Major trauma is a leading cause of morbidity and mortality worldwide with hemorrhage accounting for 40% of deaths. Acute traumatic coagulopathy exacerbates bleeding, but controversy remains over the degree to which inhibition of procoagulant pathways (anticoagulation), fibrinogen loss, and fibrinolysis drive the pathologic process. Through a combination of experimental study in a murine model of trauma hemorrhage and human observation, the authors' objective was to determine the predominant pathophysiology of acute traumatic coagulopathy. Methods: First, a prospective cohort study of 300 trauma patients admitted to a single level 1 trauma center with blood samples collected on arrival was performed. Second, a murine model of acute traumatic coagulopathy with suppressed protein C activation via genetic mutation of thrombomodulin was used. In both studies, analysis for coagulation screen, activated protein C levels, and rotational thromboelastometry (ROTEM) was performed. Results: In patients with acute traumatic coagulopathy, the authors have demonstrated elevated activated protein C levels with profound fibrinolytic activity and early depletion of fibrinogen. Procoagulant pathways were only minimally inhibited with preservation of capacity to generate thrombin. Compared to factors V and VIII, proteases that do not undergo activated protein C–mediated cleavage were reduced but maintained within normal levels. In transgenic mice with reduced capacity to activate protein C, both fibrinolysis and fibrinogen depletion were significantly attenuated. Other recognized drivers of coagulopathy were associated with less significant perturbations of coagulation. Conclusions: Activated protein C–associated fibrinolysis and fibrinogenolysis, rather than inhibition of procoagulant pathways, predominate in acute traumatic coagulopathy. In combination, these findings suggest a central role for the protein C pathway in acute traumatic coagulopathy and provide new translational opportunities for management of major trauma hemorrhage. Abstract : Using blood samples from trauma patients and a murine model of acute traumatic coagulopathy with suppressed protein C–activation, the authors demonstrated elevated activated protein C levels with increased fibrinolysis and depletion of fibrinogen. Procoagulant pathways were only minimally inhibited. Activated protein Cassociated fibrinolysis and fibrinogenolysis, rather than inhibition of procoagulant pathways, predominate in acute traumatic coagulopathy and provide new potential translational opportunities for therapy.Supplemental Digital Content is available in the text.